PENGARUH PROFITABILITAS, LEVERAGE DAN GENDER DIVERSITY TERHADAP PENGUNGKAPAN EMISI KARBON - Herinda, Farica; Masripah, Masripah; Wijayanti, A (Jurnal Akunida, 2021)
The study aims to look at the influence of profitability, leverage and gender diversity on carbon emissions disclosure. In this study, the samples used were samples from mining and agricultural companies listed on the Indonesia Stock Exchange in the period 2017 to 2019. Profitability is measured by Returns on Asset, leverage is measured by Debt to Asset and gender diversity is measured by Blau heterogeneity index. Carbon emissions disclosure is measured using an emissions disclosure checklist containing 18 items related to carbon emissions related to climate change, greenhouse gas emissions, greenhouse gas emission reduction plans, greenhouse gas emission intensity, and corporate governance. The analysis method used in this study is descriptive analysis and hypothesis test of multiple linear regression analysis with the help of STATA software version 16.0. All hypotheses in this study were rejected with the results of the study showing that profitability has a significant negative effect on the disclosure of carbon emissions. Leverage and gender diversity have no effect on the disclosure of carbon emissions.